1986
DOI: 10.1093/bja/58.9.1012
|View full text |Cite
|
Sign up to set email alerts
|

Saddle Block With Pethidine for Perineal Operations

Abstract: Saddle blockade with pethidine hydrochloride was performed in 111 patients undergoing short surgical operations on the perineum. A dose of 5% pethidine 0.5 mg kg-1 was injected to the subarachnoid space at L4-5 or L5-S1 with the patient in the sitting position. Sensory blockade was achieved in 5.28 +/- 1.43 min. This extended to the sacrococcygeal area, perineum, buttocks and posterior surface of thighs, and was followed 1-2 min later by motor blockade. During the operation the patients were stable haemodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(9 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Because of its local anaesthetic effect on peripheral nerves pethidine may be the ideal analgesic for curettage. Previous in vivo studies demonstrated that when given intrathecally pethidine was effective as the sole anaesthetic for surgery of the perineum 19 and caesarean delivery 20 . Pethidine with a short duration of action, has been widely and routinely prescribed for moderate to severe pain in medical and surgical patients 21 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Because of its local anaesthetic effect on peripheral nerves pethidine may be the ideal analgesic for curettage. Previous in vivo studies demonstrated that when given intrathecally pethidine was effective as the sole anaesthetic for surgery of the perineum 19 and caesarean delivery 20 . Pethidine with a short duration of action, has been widely and routinely prescribed for moderate to severe pain in medical and surgical patients 21 22 .…”
Section: Discussionmentioning
confidence: 99%
“…A local nerve blocking effect was also reported in human volunteers subjected to intravenous regional anaesthesia [3] or femoral nerve block [6]. Furthermore, as mentioned earlier, pethidine also has the ability to induce sensory and motor blockade when injected intrathecally in patients undergoing caesarean section [5], prostate [15] or perineal surgery [1]. The unspecific blockade lends support to a local anaesthetic action of pethidine.…”
Section: Discussionmentioning
confidence: 76%
“…This raises an interesting question. Intrathecal meperidine produces a sufficient degree of nerve block to perform surgery of the lower limbs and perineum (Acalovschi et al, 1986). This local effect of meperidine may be explained by its ability to block a variety of channels with EC 50 values under 200 μM, including voltage-activated Na+ channels, delayed rectifier K+ channels, the calcium-activated K+ channel, and the voltage-independent flicker K+ channel (Brau et al, 2000).…”
Section: Discussionmentioning
confidence: 99%